The Essence of Bengal's Ethnic Sweetmeats: An Exploratory Journey through History, Tradition, and Culture. (22nd February 2023) - Sarkar, Tanmay; Salauddin, Molla; Paul, Arindam; Choudhury, Tanupriya; Chakraborty, Runu; Imran, Faisal
Abstract : The enthralling sweet taste that mesmerizes the eastern part of India, or more specifically the undivided Bengal (West Bengal and Bangladesh) is unveiled. The ethnic sweetmeats that originated in Bengal varied over their primary ingredients, size, shape, and process of production due to variation in the context of geographical, cultural, and religious beliefs. In total, thirty-eight numbers of sweet products that are originated in Bengal are reconnoitered along with their nutritional composition and shelf life. Based on the key ingredients, the sweetmeats can be divided into nine classes, namely, chhana-based, pulse-based, fried, milk-skin-based, extruded rice-based, fermented, khoa-based, fruit-based, and sugar-based. Nutritional heritage comes along with health-related benefits to mankind; the racial sweetmeats produced in undivided Bengal have crucial medicinal and gastronomical importance. The sweetmeats are basically the assimilation of ancestral Bengali tradition, rituals, and convictions through the cascade of time. The classical and folk processing methods practiced from antediluvian times have had a prominent impression on the taste and nutritional comportment of the sweets produced. To the best of our knowledge, this article is the first attempt to scientifically document the integrity of the processing methods, nutritional content, and health benefits of traditional sweetmeats.